Dynamical Analysis of a Discrete Fractional Order Prey-Predator 3 – D System - Selvam, A.George Maria; *, Janagaraj; Dhineshbabu, R. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
t. In this paper, we propose and discuss the dynamical nature of discrete fractional orderprey – predator systems. A discretization process is applied to obtain itsdiscrete version. Fixedpoints and the asymptotic stability are investigated.Chaotic attractor, bifurcation and chaos fordifferent values of the fractional order parameter arediscussed.2000 Mathematics Subject Classification.26A33, 39A11, 39A12.